Isolated unilateral temporalis muscle hypertrophy: first case in an Indo-Aryan - Niyaf, Ali; Niraula, Kiran; Zahir, Shiara; Mushrif, Mohamed Sajuan (Nepal Journal of Neuroscience, 2020)
Unilateral hypertrophy of temporalis muscle (isolated type) is extremely rare and only 14 cases have been reported in English literature since 1990. Although no definitive etiology is identified, stress and bruxism are among the many factors are linked to it. Reported patient ages ranged from 7 years to 62 years and most of them are Caucasians. Here we report the first ever case of an Indo-Aryan ethnic patient who presented with painful swelling of the left temporal region. Temporalis muscle biopsy confirmed the diagnosis of isolated unilateral temporalis muscle hypertrophy. This case raises the importance of considering rare diagnoses such as isolated unilateral temporalis muscle hypertrophy despite the inadequate statistical data on ethnicity or geographic location of a condition.